Laparoscopic resection of hepatocellular carcinoma following liver transplantation: a video case report - Vennarecci, Giovanni; Berardi, Giammauro; Guglielmo, Nicola; Antonini, Mario; Ettorre, Giuseppe Maria (Laparoscopic Surgery, 2019)
Laparoscopy in the setting of cirrhosis has been described as having favorable outcomes compared to open in terms of collateral preservation, diminished manipulation, less fluid requirement, re-duced blood loss and transfusion rates leading to better short-term outcomes. Hepatocellular carcinoma (HCC) following liver transplantation (OLT) is frequent considering recurrence and de-novo lesions and the role of laparoscopy in this setting is unclear. In this setting, a minimally invasive approach could be indicated but should be considered with caution for the possibility of finding strong adhesions limiting the working space and because of the impossibility of performing the Pringle maneuver in case of bleeding. To the best of our knowledge, there are currently no reports of such an approach among the literature. We hereby present the video case report of a patient undergoing laparoscopic liver resection (LLR) following the diagnosis of a HCC in the liver “graft”. A 65-year-old male presented to our department for routine follow-up; He received OLT in May 2008 for liver cirrhosis HCV related and HCC. A CT scan showed a 40 mm lesion that was diag-nosed as an HCC (LIRADS classification 5). The patient was scheduled for a LLR. A 4-trocar technique was carried out using high energy device and bipolar forceps. No nasogastric tube was placed. The patient was put on clear liquids diet on postoperative day (POD) 1. On the second POD solid food intake was allowed. The drainage was removed in 3rd POD and the patient was discharged home without complications. Laparoscopic resection of HCC following liver transplantation is safe and feasible and should be considered as a first approach possibly improving outcomes.